Effect of Cryogenic Treatment on Properties of Cemented Carbides - Prucha, Vojtech; Bricin, David; Kriz, Antonin (Manufacturing Technology Journal, 2019)
The main goal of this paper is to present experiments exploring the effect of cryogenic treatment on the properties of cemented carbides. The experimental materials were chosen from three basic groups of cemented carbides with different binders and different WC grain sizes. One half of the specimens were cryogenically-treated, whereas the other half were in the as-received condition. The specimens were ground and polished using metallographic procedures. Effects of cryogenic treatment were studied by metallographic observation using light and scanning electron microscopes, by X-ray analysis of phase composition and by measuring Vickers hardness and KIC fracture toughness. It was found that residual stresses in specimen surface decreased after cryogenic treatment. The KIC fracture toughness of the specimens increased.
Keywords: Cryogenic Treatment; Cemented Carbide; Residual stress; Hardness; Phase Analysis